2014
DOI: 10.1007/s11033-014-3770-9
|View full text |Cite
|
Sign up to set email alerts
|

Clock gene variants differentiate mood disorders

Abstract: Genetic variations in clock-related genes were hypothesized to be involved to in the susceptibility of mood disorders MD (both unipolar (UPD) and bipolar (BPD) disorders). In our work we investigated role of gene variants form four core period proteins: CLOCK, ARNTL, TIM and PER3. The total sample comprised from 744 mood disorders inpatients (UPD = 229, BPD = 515) and 635 healthy voluntary controls. The 42 SNPs from four genes of interest were genotyped. We used single polymorphisms, haplotypes, SNPs interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…This demonstrates a hereditary predetermination for the association between BD and circadian problems . Indeed, it has been observed that genetic changes in circadian genes may alter circadian activity and increase the risk of BD developing …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This demonstrates a hereditary predetermination for the association between BD and circadian problems . Indeed, it has been observed that genetic changes in circadian genes may alter circadian activity and increase the risk of BD developing …”
Section: Discussionmentioning
confidence: 96%
“…Several lines of evidence suggest that the psychopathological symptoms of BD arise, in part, from impaired function of CR . In addition, an important role has been defined for variations of circadian machinery genes in changes in behavior, mood and affectivity, characteristics involved in BD …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations